Analisa Kekuatan Material BJTP P40 dan Carbon Steel AISI 1018 Sebagai Ulir Angkur Dengan Uji Torsi - A Arianto; F A Kurniawan; A Irwan (Jurnal MESIL (Mesin Elektro Sipil), 2021)
In this study, the authors conducted torsion testing to determine the mechanical properties obtained from plain reinforcing steel (BJTP) and Carbon Steel as anchor threads on tower poles. The aim is to determine the strength and toughness of a specimen for anchorage threads. The results calculated or sought in this test are shear stress (?), shear strain (?), moment of inertia (J), modulus of shear elasticity (G), and perform material comparisons. And to know the mechanical properties of the material. Ankur is a type of nail that functions to unite the upper structure with the lower function of the steel anchor, namely as a hook or foundation on a street light pole or other pile foundation. The main loading of the anchor threaded shaft on the tower pole is the torsion that occurs in the tower pole element or other loading such as tensile and compressive. The strength of the screw shaft anchor on the tower pole must be known using a torsion test tool (torque test). A torsion test is a tool designed to measure how much torsional strength can be performed during testing. anchor threaded shaft on tower pile Research results of po reinforcing steel specimens los(BJTP) compared to Carbon steel. Some research results such as moment of inertia (J) shear stress (?) shear strain (?) modulus of elasticity (G). The results show that the moment of inertia of BJTP is 2.39x10-9m4, while the moment of inertia of the Carbon specimen Steel is 2.39x10-9m4. The shear stress result from BJTP is 65.509 Mpa, while the shear stress result from Carbon Steel specimen is 62.921 Mpa. The result of BJTP shear strain is 3.705 Mpa, while the shear strain result is 3.705 Mpa of the Carbon Steel specimen is 4.120 Mpa. And the result of the modulus of elasticity of BJTP is 0.1768 Mpa, while the result of the modulus of elasticity of Carbon Steel is 0.1527 Mpa.